ሽንኩርት ከምርት ወደ ገበያ በአላማጣ - International Livestock Research Institute (International Livestock Research Institute, 2011)
ይህ ዶኪመንቴሽን በአላማጣ ወረዳ የሽንኩርት ምርት ኤክስቴንሽን ይዞ ቀርቧል፡፡ በአላማጣ ወረዳ ያሉ አርሶ አደሮችና የወረዳው ግብርና ከ IPMS (በኢትዮጵያ ምርታማነትና የገበያ ስኬት ማሻሻያ) ፕሮጄክት ጋር በመሆን የሽንኩርት ምርትን ከገበያ የማገናኘት ስራ ላይ የጋራ እንቅስቃሴ ፈጥረዋል። ይህ ዶኪመንቴሽን በአርሶ አደሩ የተደረጉ ተሞክሮዎችና በ ዕውቀት መጨበጥ አኳያ እና ገበያ ማገናኘት ላይ ያሉ ውጤቶችንና ስኬቶችን ይዞ ቀርቧል። ‘Onion: from farm-gate to market’ presents the experience of Improving Productivity and Market Success (IPMS) project on improving onion value chain in Alamata district, Tigray, Ethiopia. On this video, extension experts and farmers share their experiences of engaging in market oriented agriculture production and their experience in organizing themselves into cooperatives and creating linkage traders in urban markets. The role of the district office of agriculture and experts reflection on the alliance they formed with the IPMS and other stakeholders to facilitate market access is highlighted on this video.